2017
DOI: 10.1055/s-0036-1597973
|View full text |Cite
|
Sign up to set email alerts
|

Early Age at First Sexual Intercourse is Associated with Higher Prevalence of High-grade Squamous Intraepithelial Lesions (HSIL)

Abstract: Objective To evaluate the association of age at first sexual intercourse with the results of the cervicovaginal cytology. Study Design Observational analytical study about the prevalence of altered cervicovaginal cytology results in women aged between 18 and 34 years from a densely populated area in Brazil, during 10 years. The patients were stratified into 2 categories according to their age at first sexual intercourse (13-16 years and 17-24 years).Results From the total of 2,505,154 exams, 898,921 tests were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
0
8
0
3
Order By: Relevance
“…This finding is inconsistent with previous literature, which found that younger age at first sexual intercourse is positively associated with HPV infection, abnormal cytology, and invasive cervical cancer. [33][34][35] Notably, participants who reported first sexual encounter at >16 years were also more likely to report having two or more sexual partners in their lifetime (data not shown).…”
Section: Discussionmentioning
confidence: 94%
“…This finding is inconsistent with previous literature, which found that younger age at first sexual intercourse is positively associated with HPV infection, abnormal cytology, and invasive cervical cancer. [33][34][35] Notably, participants who reported first sexual encounter at >16 years were also more likely to report having two or more sexual partners in their lifetime (data not shown).…”
Section: Discussionmentioning
confidence: 94%
“…Early age of first intercourse is associated with an increased risk of cervical pre-malignant lesions and CC in developing countries [21][22]. This study has shown that 30.4% of middle school female student were sexually active and earliest first sexual intercourse was at 12 years and was in urban school (Figures 2 and 3).…”
Section: Sexual Exposurementioning
confidence: 70%
“…In Yaoundé, 741 (73.1%) attended grammar school and 270 (26.9%) technical middle school; in the rural town of Ndikinemeki, 242 (60.5%) attended grammar school and 58 (39.5%) technical middle school. The majority of students were aged [15-18[ in urban middle school (Yaoundé) and [18][19][20][21] in rural middle school (Ndikinemeki). Four hundred (30.4%) students were sexually active; 14 refused to answer, the youngest was 12 in urban area and 14 in rural area, all the ages were represented.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of patients aged between 20 and 24 years was also not irrelevant. On the basis of findings showing a close relation between the age of first sexual intercourse and a diagnosis of HSIL or more in young patients, screening of patients younger than 25 years ages might be beneficial.…”
Section: Findings For the Population Of Women With High‐grade Squamoumentioning
confidence: 99%